Differences in soccer kicking type identified using principal component analysis - Nakamura, T.; Miyoshi, T.; Sato, S.; Takagi, M.; Kamada, Y.; Kobayashi, Y. (Sports Engineering, 2018)
Soccer kicks are characterized by segmental and joint rotations in multiple planes, where large discrepancies between two- and three-dimensional analyses for angular measurements of soccer kicks exist. The aim of this study was to clarify the differences in motions of the lower limbs and the pelvis required to achieve a shot without rotations as compared with an instep kick. Kinematic parameters obtained from non-rotational shots and instep kicks were analyzed using principal component analysis (PCA). The results clearly demonstrated that the PCA identified the differences in the instep kick and the non-rotational shot relative to the kinematic motions of the lower limbs and the pelvis. These findings suggest that the key issue for executing the NR shot is achieving a straight-line foot trajectory in the impact phase.